ANALISIS VEGETASI PADA KAWASAN HUTAN DESA DI DESA NANGA YEN KECAMATAN HULU GURUNG KABUPATEN KAPUAS HULU - ginting, zefry arqino; Manurung, Togar Fernando; Sisillia, Lolyta (Universitas Tanjungpura, 2017)
This study aimsed to determine the structure and composition of tree species from various growth levels and to know the dominant tree species from various growth levels. The research was conducted in Village Forest Area in Nanga Yen Village, Hulu Gurung District, Kapuas Hulu Regency with 4 weeks research time in field. The method used was survey method by way of combination between path and plot. The laying of the transect line was done by purposive sampling and the laying cuted the contour direction. The number of observation paths consisted of 6 lines, with each path length of 500 M. Data was analysed by calculating the importance value index (INP), the dominance index (c), Index of species diversity (H'), and abundance index (e) at the level of pole and tree sapling. The results of the data analysis showed that the dominant species based on the Importance Value Index (IVI) for all growth rates are Keladan (Dryobalanops oblongifolia), Ubah Putih (Syzygium sp) and Ubah Merah (Syzygium sp). Based on the the dominance Index (c) was categorized as low because the value of C < 0.5, Index of species diversity (H'), was very high because the H'> 1 and the species abundance (e) were categorized almost equally because the value e approaches 1 (one). Keywords: Analysis of Vegetation, Kapuas Hulu, Forest Structure and Composition, Village Forest